2016
DOI: 10.1007/s00429-016-1308-8
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise induces structural alterations in the hippocampal astrocytes: exploring the role of BDNF-TrkB signaling

Abstract: While it has been known that physical activity can improve cognitive function and protect against neurodegeneration, the underlying mechanisms for these protective effects are yet to be fully elucidated. There is a large body of evidence indicating that physical exercise improves neurogenesis and maintenance of neurons. Yet, its possible effects on glial cells remain poorly understood. Here, we tested whether physical exercise in mice alters the expression of trophic factor-related genes and the status of astr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 68 publications
2
42
1
Order By: Relevance
“…Many mechanisms are involved in such adaptation, exerting significant regulatory control over many facets of a neuronal function and leading to the biological effects of the hippocampus, including cognitive functioning and neurogenesis (Chou et al, 2018;Firth et al, 2018;Liu and Nusslock, 2018;Hill and Polk, 2019). A previous study has shown that treadmill exercise in mice increases BDNF expression by regulating BDNF mRNA and protein expression in the hippocampus (Fahimi et al, 2017). Similar changes were observed in the NT group in the present study.…”
Section: Discussionsupporting
confidence: 86%
“…Many mechanisms are involved in such adaptation, exerting significant regulatory control over many facets of a neuronal function and leading to the biological effects of the hippocampus, including cognitive functioning and neurogenesis (Chou et al, 2018;Firth et al, 2018;Liu and Nusslock, 2018;Hill and Polk, 2019). A previous study has shown that treadmill exercise in mice increases BDNF expression by regulating BDNF mRNA and protein expression in the hippocampus (Fahimi et al, 2017). Similar changes were observed in the NT group in the present study.…”
Section: Discussionsupporting
confidence: 86%
“…Under the influence of the training process, increased BDNF expression in the hippocampus, cerebral cortex, ST, brainstem, and spinal cord was observed [131,174,179,181,182]. Animal studies have shown that long-term endurance training increased both TrkB receptor and TH expression in structures involved in extrapyramidal movement regulation, i.e., in the ST and midbrain [128,129,179,[183][184][185]. As previously mentioned, the key element of neurotrophin-related neuroprotection is the IP3/Akt kinase pathway [186].…”
Section: Possible Mechanisms Underlying the Protective Effect Of Bndfmentioning
confidence: 87%
“…In addition, following spinal cord injury, TrkB.T1 knockout astrocytes have slower migration/proliferation in response to BDNF and downregulated migration and proliferation pathways (Matyas et al, 2017). Interestingly, BDNF, TrkB, and astrocytic territory are all increased by exercise (Fahimi et al, 2017), which enhances cognition (Gomez-Pinilla and Hillman, 2013).…”
Section: Discussionmentioning
confidence: 99%